A comparison of silver staining protocols for detecting DNA in polyester-backed polyacrylamide gel - Qiu,Shanlian (2012)
Eight silver-staining protocols were applied to detect DNA in polyester-backed gels to select the optimal. Results showed important differences in staining quality and that four methods were well-suited for TGGE gels due to high sensitivity and low background, including the Bassam et al. methods, the manufacturer method and our improved method.